Spatio-Temporal Assessment of the European Hake (Merluccius merluccius) Recruits in the Northern Iberian Peninsula - Izquierdo, Francisco; Paradinas, Iosu; Cerviño, Santiago; Conesa, David; Alonso-Fernández, Alexandre; Velasco, Francisco; Preciado, Izaskun; Punzón, Antonio; Saborido-Rey, Fran; Pennino, Maria Grazia (Frontiers in Marine Science, 2021)
The protection of fish nurseries has been recognized as a useful tool to efficiently manage fisheries given that protected areas enhance the recruitment of target species. To identify and locate potential nursery areas, a solid understanding of species-environment relationships and their spatio-temporal dynamics is needed. Within this context, in this study we assess where European hake (Merluccius merluccius) recruits persistently aggregate in the northern continental shelf of the Iberian Peninsula. Hake recruit data collected during scientific trawl surveys between 2005 and 2016 were analyzed using Bayesian hurdle hierarchical spatio-temporal models, considering the environmental variables bathymetry, sea bottom temperature and salinity. Additionally, three different spatio-temporal structures (i.e., persistent, progressive, or opportunistic) were compared to assess the temporal persistence of nurseries over time. Among all the environmental variables analyzed, bathymetry was the most important. The preferential habitat of recruits was found to be within a bathymetric range of 120–200 m. Our findings clearly show that there is a temporally persistent main nursery located along the continental shelf of the Artabrian gulf (off La Coruña) in addition to several areas with high aggregations of hake recruits but with strong inter-annual variability. We argue that the analytical framework applied in this study allowed us to identify European hake nurseries in the northern continental shelf of the Iberian Peninsula, as well as their spatio-temporal fluctuations throughout the study period (2005–2016), and to assess which environmental factors, among bathymetry, sea bottom temperature and salinity, influence the occurrence and abundance of recruits in the study area. Results of our models also produce a new abundance index that could be useful for improving traditional stock assessment models.